INTEGRASI MEDIA ULAR TANGGA DALAM PEMBELAJARAN MADRASAH DINIYYAH DI PONDOK PESANTREN - Istiqomah, Indah; Aulia, Umu Intan; Annabila, Sayyidah Rahmah; Musyafa, Abriel Ainani; Idawati, Khoirotul; Hanifudin, Hanifudin (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KH. EZ. Muttaqien Purwakarta, 2026)
This study aims to analyse the integration of the Snakes and Ladders game as an innovative strategy in Diniyyah learning in Islamic boarding schools. The research background is based on the need for contemporary 21st-century learning that is more interactive, engaging, and effective in increasing student involvement in understanding religious material. The type of research used is R&D (Research and Development), by adopting the ADDIE development model to produce learning media products. The results show that integrating the Snakes and Ladders game with several Diniyyah lessons, such as Tajwid, Nahwu, Shorof, and Fiqh, can increase learning motivation, strengthen the understanding of basic religious and scientific concepts, and foster positive interactions between students. This media integration is also in line with the gamification approach that emphasises active and collaborative learning experiences. Thus, the snakes and ladders game can be used as an alternative, creative learning medium that is relevant to improving the quality of Diniyyah learning in Islamic boarding schools.